2017
DOI: 10.1371/journal.pone.0179318
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of trace metal content in the developing zebrafish embryo

Abstract: Trace metals are essential for health but toxic when present in excess. The maintenance of trace metals at physiologic levels reflects both import and export by cells and absorption and excretion by organs. The mechanism by which this maintenance is achieved in vertebrate organisms is incompletely understood. To explore this, we chose zebrafish as our model organism, as they are amenable to both pharmacologic and genetic manipulation and comprise an ideal system for genetic screens and toxicological studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Brain copper concentrations were inversely correlated with age. It is worth noting that measurements of total copper levels may not necessarily reflect the biologically active metal pools [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brain copper concentrations were inversely correlated with age. It is worth noting that measurements of total copper levels may not necessarily reflect the biologically active metal pools [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cu, Mn, and Zn metal content in early embryos has been suggested to be set by the maternal contribution and only increases once zebrafish develop to the stage where they can acquire nutrients through the diet or the environment. 57 The concentrations of Cu, Mn, and Zn reported in the study of Thomason et al indicated that relatively low concentrations are required for fish younger than 30 dpf, suggesting that the concentrations of the CRWS shown in this study might be sufficient for normal biological processes in larval and juvenile zebrafish.…”
Section: Discussionmentioning
confidence: 50%
“…Zebra sh has been widely used to investigate the effects of Mn, including a manganism model (Altenhofen et , 2020). It has been shown that Mn content levels increase in the zebra sh after 5 days-post-fertilization (dpf), when they start to feed from external sources (Thomason et al, 2017). Interestingly, at this developmental stage the larvae increase sensitivity to Mn exposure (Altenhofen et al, 2017;Bakthavatsalam et al, 2014;Hernández et al, 2015;Tu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%